2021
DOI: 10.36685/phi.v7i2.402
|View full text |Cite
|
Sign up to set email alerts
|

The obedience of medical personnel to using personal protective equipment in preventing the transmission of COVID-19 at a private hospital in Indonesia

Abstract: Background: As one of the vulnerable groups to be infected by COVID-19, healthcare workers are required to obey the hospital rules and protocols. However, it may remain challenging for them, especially related to the provision of using personal protective equipment.Objective: This study examined the obedience of medical personnel to personal protective equipment in preventing the transmission of COVID-19 at PKU Muhammadiyah Hospital Yogyakarta, Indonesia.Methods: This cross-sectional study examined 259 medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The rest of the predictors which were sex, having a personal income, and receiving food or agricultural inputs from the government were not significantly associated with being unable to eat healthy and nutritious food. In line with the result of this study, a previous study in Indonesia among health personnel did not show an association between sex and awareness to care about COVID-19, including how the person accesses healthy and nutritious food [28]. Table 3 displays the result of binary logistic regression.…”
Section: Resultssupporting
confidence: 82%
“…The rest of the predictors which were sex, having a personal income, and receiving food or agricultural inputs from the government were not significantly associated with being unable to eat healthy and nutritious food. In line with the result of this study, a previous study in Indonesia among health personnel did not show an association between sex and awareness to care about COVID-19, including how the person accesses healthy and nutritious food [28]. Table 3 displays the result of binary logistic regression.…”
Section: Resultssupporting
confidence: 82%
“…Similar to a study in Yogyakarta, Indonesia, that found 35.9% of their participants have poor obedience to use personal protective equipment. This study also revealed that their poor compliance due to their attitude to disease prevention was poor (Hartuti et al, 2021). This may be due to the lack of equipment, which has direct or indirect negative impacts behaviour and adherence in preventing COVID-19.…”
Section: Discussionmentioning
confidence: 76%
“…A previous study in Turkey found that pregnant women in the second and third trimesters received the vaccine more often than pregnant women in the first trimester (Goncu Ayhan et al, 2021). As a result of the study, there were 3 articles that found a relationship between attitudes and acceptance of the COVID-19 vaccine in pregnant women (Anjelika et al, 2022;Budiarti et al, 2021;Hartuti et al, 2021;Zada, 2022).…”
Section: Resultsmentioning
confidence: 90%